Three decades of The Necks: Reciprocal Patterns of Improvised Music and Organisational Behaviour - Rose, Jeremy (Critical Studies in Improvisation / Études critiques en improvisation, 2022)
This article explores the nature of organisational behaviour within a long-standing improvised music group and its reciprocal relationship with their musical practice. It uses ideas from Ingrid Monson (1996) relating to social activities expressing the values and aesthetics of musical practice and adopts research findings from business management literature, in particular Kenneth Bettenhausen’s (1991) notion that the task patterns of a group play a role in shaping attitudes and behaviour, informing our understanding of the way improvisational music practices correlate with social and organisational behaviour.The Australian piano trio, The Necks, perform minimalist extended improvisations with ritual-like patterns in performance and social behaviour. Being self-managed with the same line-up since 1987, they present a unique case study in how a band’s organisational behaviour has a mutual relationship to its musical practice. This study traces out their organisational patterns to show how these have developed in tandem with an improvisational ethos in which members undertake slowly evolving group minimalist improvisations guided by an unspoken set of behavioural patterns with adaptable parameters for change. The findings reveal an underlying narrative of tension between group homogeneity and individual autonomy, experiences of group flow, the use of varying modes of communication for varying contexts, similarities between their musical improvisation parameters and their social interaction, and strategies for implementing change and innovation. The article sketches how their social and organisational behaviour converges with their musical process: a slow rate of change, effortless, and yet with a long arc of possibilities.